The Female Sex Work Industry in a District of India in the Context of HIV Prevention. (30th December 2012) - Buzdugan, Raluca; Halli, Shiva S.; Hiremath, Jyoti M.; Jayanna, Krishnamurthy; Raghavendra, T.; Moses, Stephen; Blanchard, James; Scambler, Graham; Cowan, Frances
Abstract : HIV prevalence in India remains high among female sex workers. This paper presents the main findings of a qualitative study of the modes of operation of female sex work in Belgaum district, Karnataka, India, incorporating fifty interviews with sex workers. Thirteen sex work settings (distinguished by sex workers' main places of solicitation and sex) are identified. In addition to previously documented brothel, lodge, street, dhaba (highway restaurant), and highway-based sex workers, under-researched or newly emerging sex worker categories are identified, including phone-based sex workers, parlour girls, and agricultural workers. Women working in brothels, lodges, dhabas, and on highways describe factors that put them at high HIV risk. Of these, dhaba and highway-based sex workers are poorly covered by existing interventions. The paper examines the HIV-related vulnerability factors specific to each sex work setting. The modes of operation and HIV-vulnerabilities of sex work settings identified in this paper have important implications for the local programme.